Analysis of Two Different Translations of the Tragedy "Hamlet" into Uzbek - Munavvar Kurbanova Esonalievna (International Journal on Integrated Education, 2021)
In this article, we focus on the analysis of the translations of Shakespeare's tragedy "Hamlet" and the preservation of the author's style. Although there are many translation options for this tragedy, we have analyzed the texts of Maqsud Shaykhzoda and Jamal Kemal. In this case, the first option (translation by Maqsud Shaykhzoda) is a translation from Russian, and the second (translation by Jamal Kamal) is a direct translation from English. Examples were also given of Russian versions of the work in order to illustrate the effect of the mediating language on the preservation or departure of the author's style in the process of translation into Uzbek.